Stakeholder Collaboration through the Pentahelix Model in the Tetebatu Nature Fest 2024 Event - Walid Sugandi, Yogi Birrul; Adi Junaidi, Muhammad (JMET: Journal of Management Entrepreneurship and Tourism, 2025)
The Tetebatu Nature Fest 2024 is the inaugural event aimed at branding Tetebatu Village, East Lombok, as an international nature tourism destination. This study seeks to analyze the role of the pentahelix model, which involves the government, academia, businesses, communities, and media in the implementation of this event. Additionally, it aims to identify challenges and strategic solutions to enhance stakeholder collaboration effectiveness. A qualitative approach was employed, utilizing interviews, observations, and document analysis. The findings indicate that the pentahelix collaboration positively contributes to tourism promotion, local community empowerment, and cultural preservation. However, challenges such as lack of stakeholder coordination and resource limitations need to be addressed. This study concludes that strengthening coordination, fostering active community involvement, and diversifying promotional strategies are essential. The research provides significant contributions to the development of collaborative-based tourism to establish a sustainable tourism destination